Segalá y Estalella : cien años de la Ilíada castellana - Sánchez-Jiménez, Francisco (Universidad de Málaga. Facultad de Filosofía y Letras, 2008)
Con ocasión del centésimo aniversario de la publicación de la traducción al castellano de la Ilíada de Luis Segalá y Estalella (Barcelona 1908), se revisan aquí algunos aspectos del contexto cultural en el que se enmarca este trabajo, así como del método utilizado, que sitúan a la versión de Segalá entre las más importantes aportaciones de la primera mitad del siglo XX al desarrollo de los estudios clásicos en España.

Coinciding with the hundredth anniversary of the publication of Luis Segalá Estalella’s translation of Homer’s Iliad, (Barcelona 1908), this article revises some aspects of the cultural context in which this work was developed, as well as the method followed, both of which result in Segala’s translation being considered one of the most important contributions to Classic Studies in Spain during the first half of the 20th Century.
Keywords: Ilíada - Traducción